2007
DOI: 10.1093/ietcom/e90-b.7.1801
|View full text |Cite
|
Sign up to set email alerts
|

A Robust and Fast Imaging Algorithm with an Envelope of Circles for UWB Pulse Radars

Abstract: UWB pulse radar systems are promising as high-resolution imaging techniques for household or rescue robots. We have already proposed a fast imaging algorithm called SEABED based on a reversible transform BST(Boundary Scattering Transform) between the received signals and the target shape. However, the image obtained with SEABED deteriorates in a noisy environment because it utilizes derivative of received data. In this paper, we propose a robust and fast imaging method with an envelope of circles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 4 publications
0
38
0
Order By: Relevance
“…We have developed another 2-D imaging algorithm with envelope of circles (Envelope method) [11], and confirmed that it could suppress fluctuations due to derivative operations without data smoothing. This method utilizes the principle that the target boundary can be expressed as the outer or inner envelope of the circles, whose center is (X, 0) and radius is Z, in a mono-static radar.…”
Section: Discussion On Envelope Methods With Array Antennasmentioning
confidence: 69%
“…We have developed another 2-D imaging algorithm with envelope of circles (Envelope method) [11], and confirmed that it could suppress fluctuations due to derivative operations without data smoothing. This method utilizes the principle that the target boundary can be expressed as the outer or inner envelope of the circles, whose center is (X, 0) and radius is Z, in a mono-static radar.…”
Section: Discussion On Envelope Methods With Array Antennasmentioning
confidence: 69%
“…A more efficient algorithm is the SEABED onset, achieving an imaging with the outstanding feature to determine the direction of Radar responses, based on changes of the roundtrip times (RTT). The Inverse Boundary Scattering Transform (IBST), proposed in [15,16] as a part of SEABED is given by:…”
Section: In-wall Imaging and Object Recognition Onsetmentioning
confidence: 99%
“…The presented method is based on the Envelope algorithm originally proposed by Kidera et al in [20]. The Envelope algorithm was selected for breast surface reconstruction over the approaches considered in [11][12][13][14][15][16][17][18] since it offers highaccuracy surface reconstructions of arbitrary-shaped targets in scenarios considering various noise levels [20,21].…”
Section: Introductionmentioning
confidence: 99%